2017
DOI: 10.1039/c6sm02678h
|View full text |Cite
|
Sign up to set email alerts
|

Phase behaviour and gravity-directed self assembly of hard convex spherical caps

Abstract: We investigate the phase behaviour and self-assembly of convex spherical caps using Monte Carlo simulations. This model is used to represent the main features observed in experimental colloidal particles with mushroom-cap shape [Riley et al., Langmuir, 2010, 26, 1648. The geometry of this non-centrosymmetric convex model is fully characterized by the aspect ratio χ * defined as the spherical cap height to diameter ratio. We use NPT Monte Carlo simulations combined with free energy calculations to determine the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
9
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 107 publications
2
9
2
Order By: Relevance
“…3 missing in the previous works [28], as by reducing the free energy of our crystal phase by 1 2 ln 2k B T per particle, we obtain the same phase boundaries as in Ref. [24].…”
supporting
confidence: 54%
See 2 more Smart Citations
“…3 missing in the previous works [28], as by reducing the free energy of our crystal phase by 1 2 ln 2k B T per particle, we obtain the same phase boundaries as in Ref. [24].…”
supporting
confidence: 54%
“…These are substantially higher than the values obtained in Ref. [24], and the reason is the last term of Eq. 3 missing in the previous works [28], as by reducing the free energy of our crystal phase by 1 2 ln 2k B T per particle, we obtain the same phase boundaries as in Ref.…”
contrasting
confidence: 53%
See 1 more Smart Citation
“…The phase behavior of bowl‐shaped (or cap‐shaped) particles has been addressed extensively with computer simulations . Marechal et al showed in experiments supported by simulations that entropy can drive stacking of indented colloids at the mesoscale .…”
Section: Introductionmentioning
confidence: 99%
“…When the indentation in the bowl becomes shallow, a different aggregation phenomenon is observed. For example, contact lens-like particles modelled as non-convex spherical caps, show multiple phases behavior, ranging from a liquid crystalline nematic phase to cluster-like aggregates 105,106 depending on the curvature of the particles, with the aggregates being remarkably different to the structures observed in convex-spherical caps 102,[107][108][109] .…”
Section: Shape Complementarity: Lock-and-key Colloidsmentioning
confidence: 99%